Penguatan Pendidikan Karakter melalui Strategi Pembelajaran PAI Berbasis Kepesantrenan (Journal Of Islamic Education And Pesantren, 2025)
Strengthening character education is one of the major challenges in Islamic Religious Education (IRE), particularly at the Madrasah Tsanawiyah level, which represents a crucial phase in students’ moral development. This study aims to analyze the strengthening of character education through pesantren-based IRE learning strategies at Madrasatul Qur’an Islamic Junior Secondary School (Madrasah Tsanawiyah) in Tebuireng, Jombang. The research employed a qualitative approach with a case study design. The research subjects included the head of the madrasah, the vice principal for student affairs, IRE teachers, and students. Data were collected through observation, in-depth interviews, and documentation, and were analyzed interactively through data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that pesantren-based IRE learning strategies—such as the implementation of bandongan and sorogan methods, congregational worship habituation, Qur’an memorization (tahfidz) programs, and the strengthening of adab within pedagogical relationships—play an effective role in shaping students’ discipline, responsibility, honesty, and independence. These strategies facilitate sustainable value internalization through repetitive and consistent pedagogical practices. The study concludes that character education can be strengthened more effectively when IRE learning strategies are inherently integrated with pesantren culture and consistently implemented in everyday madrasah life.